Water Safety in California Public Schools Following Implementation of School Drinking Water Policies - Umunna, Isioma L. (Prev Chronic Dis, 2020)
INTRODUCTION: Recent legislation requires public and charter schools in California to test drinking water for lead. Our objective was to describe 1) results from this testing program in the context of other available water safety data and 2) factors related to schools and water utilities associated with access to safe drinking water in schools. METHODS: Our study focused on a random sample of 240 California public and charter schools. We used multivariable logistic regression, accounting for clustering of tested water sources in schools, to examine school-level factors associated with failure to meet lead-testing deadlines and any history of water utility noncompliance. RESULTS: Of the 240 schools, the majority (n = 174) tested drinking water for lead. Of the schools tested, 3% (n = 6) had at least 1 sample that exceeded 15 parts per billion (ppb) (California action level) and 16% (n = 28) exceeded 5 ppb (bottled water standard). Suburban schools had lower odds of being served by noncompliant water systems (OR = 0.17; CI, 0.05–0.64; P = .009) than city schools. Compared with city schools, rural schools had the highest odds of not participating in the water testing program for lead (OR = 3.43; CI, 1.46–8.05; P = .005). Hallways and common spaces and food services areas were the most frequent school locations tested; one-third of all locations sampled could not be identified. CONCLUSION: In our study, geography influenced access to safe drinking water in schools, including both water utility safety standards and school lead-testing practices. Considerations for improving the implementation of state lead-testing programs include establishing priority locations for sampling, precisely labeling samples, and developing well-defined testing and reporting protocols.